Post 911 Islamist Terrorism in Bangladesh: Causes and Legal Measures Taken by the Law Enforcement Agencies - Sheikh Md. Abdullah Bin Kalam (Journal of Research in Social Science and Humanities, 2025)
The emergence of Islamist Terrorism had defined the current era when in the name of Islam, most horrifying terrorist incidences of all time occurred killing thousands of people in the previous two decades has caused this vast devastation. After the incidence of 9/11 attack in the US and Bangladesh has also witnessed the most gruesome terrorist attacks, targeted killings and several small-scale terrorist incidences by Islamist Jihadists. This study focuses on the actual reasons that caused the emergence of Islamist terrorism in Bangladesh post 9/11 and initiatives or the measurements taken by the LEAs of Bangladesh. The research includes semi-structured interviews of ten participants from a different professional background. The research generated several critical facts. Political Islam, Ideology of Islamism, deprivation in every aspect and misinterpretation of Islam are the vital factors for emerging Islamist terrorism in Bangladesh post 9/11. Steps taken by the government or LEAs in response to Islamist terrorism are successful in most of the cases. Enactment of a certain law, prevention of terrorist financing, establishment of different operational units of LEAs and the efficacy of intelligence units are crucial to success in fighting against terrorism. This research recommends that the actual essence of Islam needs to be taught to the general people. Besides, employment opportunity has to be created, and terrorist financing has to be stopped. The recommendations for the LEAs are that they should emphasize on cooperation with the intelligence units, providing counter-narratives to terrorists, friendly attitudes with terrorists, being IT expert and preventing terrorist financing.